2016
DOI: 10.1038/srep18836
|View full text |Cite
|
Sign up to set email alerts
|

Directional Movement of Droplets in Grooves: Suspended or Immersed?

Abstract: The behavior of droplets trapped in geometric structures is essential to droplet manipulation applications such as for droplet transport. Here we show that directional droplet movement can be realized by a V-shaped groove with the movement direction controlled by adjusting the surface wettability of the groove inner wall and the cross sectional angle of the groove. Experiments and analyses show that a droplet in a superhydrophobic groove translates from the immersed state to the suspended state as the cross se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 42 publications
2
58
0
Order By: Relevance
“…In summary, when the inner walls of the V-shaped groove are hydrophobic or superhydrophobic, the upper meniscus of the suspended droplet is the leading meniscus while V drop changes. This expectation matches the experimental results from a previous study 6 well. Present study also demonstrated this expectation experimentally.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In summary, when the inner walls of the V-shaped groove are hydrophobic or superhydrophobic, the upper meniscus of the suspended droplet is the leading meniscus while V drop changes. This expectation matches the experimental results from a previous study 6 well. Present study also demonstrated this expectation experimentally.…”
Section: Resultssupporting
confidence: 93%
“…The radius of the curvature of the upper meniscus is expressed as Therefore, when a droplet is gently placed on the surface, the upper and lower menisci are convex, because θ s > 90°. In addition, the droplet is almost spherical to minimize the surface energy 6 . Under these conditions, θ u = θ d .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such phenomena can be helpful for water harvesting induced by condensation, 19 to transport liquid droplets in micro/nano uidic systems 20 and to produce a liquid drop of a desired size. 21 The spontaneous propulsion of liquid droplets bridged between NPSs is usually observed in hydrophilic surfaces but the underlying physical principal of such a phenomenon is still not clear. 22 In one of the studies it was observed that the dihedral angle of two NPSs plays a crucial role in deciding the stability of the liquid bridge.…”
Section: Introductionmentioning
confidence: 99%